Acidized Poly(vinyl alcohol) Coated Capillary in Electrophoresis† - Hua Mei, Zhen; Lin Li, Xiao (Asian Journal of Chemistry, 2010)
In this work, a coated capillary is fabricated physically. The coating liquid contained poly(vinyl alcohol) and citric acid at the concentration of 1 % (w/v) and 0.1 mol/L, respectively. The capillary coating resulted in a good effect of preventing protein absorption on capillary wall as performing a capillary electrophoresis with amperometric detection.